Government Internal Control as a Moderator of the Effect of Regional Financial Accounting Systems on Accountability - Siti Munawaroh; Muhammad Bayu; Djupiansyah Ganie; Nakisha Iqfah Alfada; Dawami Buchori; Yohanes Sri Guntur (LP2M IAIN Palopo, 2025)
The objective of this study is to examine the effect of the regional financial accounting system on the accountability of regional financial management at the Berau Regional Financial Management Agency (BPKAD), and to assess the moderating role of the government’s internal control system in this relationship. Primary data were obtained from 67 employees of BPKAD Berau through structured questionnaires. Data analysis employed validity and reliability tests, classical assumption tests, simple linear regression, t-tests, the coefficient of determination, and Moderated Regression Analysis (MRA). The findings reveal that the regional financial accounting system has a positive and significant impact on financial management accountability (t = 2.903 > 1.997, p = 0.005 < 0.05). Moreover, the implementation of the government’s internal control system strengthens this relationship, as indicated by a significant moderating effect (p = 0.038 < 0.05). The inclusion of the internal control system increases the explanatory power of the model by 41.1%, underscoring its importance in enhancing accountability within regional financial management.